Labeling Discourse to Build Academic Persona - Bordet, Geneviève (Journal of Academic Writing, 2015)
Academic research is an increasingly competitive activity and scientific writers are under the constant pressure of getting published. Getting past the screening device of the scientific abstract is widely based on the ability to create a discourse that is perceived as coherent, considering the target discourse community and the communicative intention. This study focuses on the use of general ‘labeling’ nouns as a factor of coherence and rhetorical persuasion in scientific abstracts, with specific interest in terms that are determined by an anaphoric ‘this’. Based on the study of PhD abstracts written in English by English and French applicants in several disciplines, my research aims to identify the factors of success and failure in the handling of this device by native and non-native writers. Labeling nouns are identified and semantically classified for each discipline, according to linguistic origin. Case studies show that success requires adequate lexical choice of labeling nouns. It is also based on an appropriate semantic and syntactic connection between the selected labeling noun and the segment it refers to, which requires sufficient general and scientific language proficiency. Didactic applications are then offered in order to raise scientific writers’ awareness of the impact of this type of cohesive device on their credibility.